Factors That Influence the Occurrence Rheumatic Heart Disease (RHD) in the Cardiology Unit, 2024 - Santos Ximenes, Herminia dos; Maria Ximenes, Herminia; Natalino Corte Real Araújo, Artur; Oqui, Maximiano; Costa Fernandes, Manuel da; Evaristo Obeno, Olandino; Paula Maria A. da Silva, Ana (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: 15.6 million people have suffered from rheumatic heart disease in all countries and this disease caused a high mortality rate of 200.00 and a high incidence of this disease from 5-14 years for men in 162 up to100.000 deaths and for women in 228 to 100.00 were dead. According to cardiology Herculano Seixas, in 2023 there were 480 patiens with rheumatic heart disease, the majority of whom were young marry have suffered from the disease at the age of >20 years, and are currently being treated at the referral hospital and the HNGV. Objective: Identification Factors that influence the occurrence of Rheumatic Heart Disease (RHD) in the polyclinic Cardiology, the National Hospital Guido Valadares. Method: In this research using the quantitative analysis method with a cross sectional approach. Results and Discussion: Bazed on the rezultanalyzes test statistic Sperman Rank P value 0,000 demonstrates that value is less than 0,05 means that influence between factor enviroment the occurrence of Rheumatic Heart Disease and result with correlation value r = 0,540 which located between 0,500-0,774 category to strong Correlation, and factor nutrition that is significant P value 0,000 demonstrates that value is less than 0,05 means that influence between factor nutrition the occurrence of Rheumatic Heart Disease and result with correlation value r = 0,828 which located between 0,800-0,990 category is the strongest Correlation. And factor socio economic that is significant P value 0,000 demonstrates that value is sless than 0,05 means that influence between factor socio economy the occurrence of Rheumatic Heart Disease and result with correlation value r = 0,624 which located between 0,600-0,775 category is the strong Correlation. Conclusion: This survey sample has a positive and significant influence between factor environment, nutrition, socio economic the occurrence of Rheumatic Heart Disease